Long-Suffering of Diabetes Mellitus and Hospital Readmission among Adult with Type 2 Diabetes Mellitus : A Multicenter Study - Restika, Indah; Sulfikar, Andi; Wijayaningsih, Kartika Sari; Tawil, Selviana (Alta Dharma Publisher, 2023)
Background: Type 2 diabetes mellitus is a chronic metabolic disease with abnormal glucose metabolism, constituting a complex health problem. As a chronic disease, people with diabetes mellitus have a high hospital hospitalization risk. Objective: This study aims to examine the correlation between diabetes mellitus duration and the incidence of hospital readmission in individuals with type 2 diabetes mellitus. Method: This study was a multicenter-based cross-sectional survey. This study was conducted in 5 hospitals in Makassar City, South Sulawesi. The research sample was 291 patients with diabetes mellitus, who were selected using a purposive sampling technique. Result: 207 respondents (71.1%) have had diabetes mellitus for 1-5 years and have been readmitted, while ten respondents (3.4%) have had diabetes mellitus for 6-10 years and have been readmitted. Meanwhile, two respondents (0.7%) who have had diabetes for more than ten years have not been readmitted. The Chi-square test resulted in a score of 0.026 (<0.05). Conclusion: Diabetes mellitus significantly impacts the risk of hospital readmission in Makassar City. Patients who have had diabetes for longer tend to comprehend the disease process and have better self-management. Recommendation: diabetes control should be improved in patients who have had diabetes for a long time to reduce readmissions. Future research should focus on developing approaches to effectively preventing hospital readmission incidents